Detection of RAS mutations in circulating tumor DNA: a new weapon in an old war against colorectal cancer. A systematic review of literature and meta-analysis. (September 2019) - Galvano, Antonio; Taverna, Simona; Badalamenti, Giuseppe; Incorvaia, Lorena; Castiglia, Marta; Barraco, Nadia; Passiglia, Francesco; Fulfaro, Fabio; Beretta, Giordano; Duro, Giovanni; Vincenzi, Bruno; Tagliaferri, Pierosandro; et al.
Background: Tissue evaluation for RAS (KRAS or NRAS) gene status in metastatic colorectal cancer (mCRC) patients represent the standard of care to establish the optimal therapeutic strategy. Unfortunately, tissue biopsy is hampered by several critical limitations due to its invasiveness, difficulty to access to disease site, patient's compliance and, more recently, neoplastic tissue spatial and temporal heterogeneity. Methods: The authors performed a systematic literature review to identify available trials with paired matched tissue and ctDNA RAS gene status evaluation. The authors searched EMBASE, MEDLINE, Cochrane, www.ClinicalTrials.gov, and abstracts from international meetings. In total, 19 trials comparing standard tissue RAS mutational status matched paired ctDNA evaluated through polymerase chain reaction (PCR), next generation sequencing (NGS) or beads, emulsions, amplification and magnetics (BEAMing) were identified. Results: The pooled sensitivity and specificity of ctDNA were 0.83 (95% CI: 0.80–0.85) and 0.91 (95% CI: 0.89–0.93) respectively. The pooled positive predictive value (PPV) and negative predictive value (NPV) of the ctDNA were 0.87 (95% CI: 0.81–0.92) and 0.87 (95% CI: 0.82–0.92), respectively. Positive likelihood ratio (PLR) was 8.20 (95% CI: 5.16–13.02) and the negative likelihood ratio (NLR) was 0.22 (95% CI: 0.16–0.30). The pooled diagnostic odds ratio (DOR) was 50.86 (95% CI: 26.15–98.76), and the area under the curve (AUC) of the summary receiver operational characteristics (sROC) curve was 0.94. Conclusion: The authors' meta-analysis produced a complete and updated overview of ctDNA diagnostic accuracy to test RAS mutation in mCRC. Results provide a strong rationale to include the RAS ctDNA test into randomized clinical trials to validate it prospectively.